Survey of users of TOPS, an internet-based system to prevent healthy subjects from over-volunteering for clinical trials...The Over-volunteering Prevention System - Boyce, M.; Walther, M.; Kirk, J.; Smith, S.; Warrington, S. (European Journal of Clinical Pharmacology, 2013)
Objective: To analyse users' experience of TOPS, an internet-based system that helps UK clinical research units to prevent healthy volunteers from participating in more than one non-therapeutic trial simultaneously, or starting a second trial too soon after the first. Methods: We sent to all units that currently use TOPS an anonymous questionnaire comprising 18 questions about the effectiveness and ease of use of the system. Results: Of 35 units that currently use TOPS, 31 (85.7 %) returned questionnaires. Most users find TOPS easy to use, had increased their detection rate of over-volunteering, and had rejected subjects as a result of using TOPS. A GP reply alone is not enough to prevent over-volunteering. Ethics committees, the MHRA and sponsors know about TOPS and support its use. Conclusions: The results confirm that TOPS does prevent healthy subjects from over-volunteering. Consequently, the Health Research Authority has agreed to take over the management of TOPS. Ethics committee approval of a phase 1 trial and MHRA accreditation of the unit will henceforth be conditional on consistent and proper use of TOPS. That should enhance its effectiveness and improve the safety of volunteers in non-therapeutic trials in the UK.